2010
DOI: 10.1051/0004-6361/201014187
|View full text |Cite
|
Sign up to set email alerts
|

Ages and luminosities of young SMC/LMC star clusters and the recent star formation history of the Clouds

Abstract: Aims. In this paper we discuss the age and spatial distribution of young (age < 1 Gyr) Small Magellanic Cloud (SMC) and Large Magellanic Cloud (LMC) clusters using data from the Magellanic Cloud Photometric Surveys. Luminosities are calculated for all age-dated clusters. Methods. The ages of 324 and 1193 populous star clusters in the SMC and the LMC were determined fitting Padova and Geneva isochrone models to their resolved color-magnitude diagrams. The clusters cover an age range between 10 Myr and 1 Gyr in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
220
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(245 citation statements)
references
References 91 publications
22
220
2
1
Order By: Relevance
“…4 we also report the age range covered by each evolutionary stage in our CMDs, although these are just estimates which do not take into account the spread of stars due to photometric errors. The youngest populations (a few Myr up to ∼100 Myr) in dwarf irregular galaxies are generally found in concentrated, actively star forming regions, which are located in the center as well as in offset knots (see, e.g., van Dyk et al 1998;Glatt et al 2010). This is clearly observed in the MS and/or BL/RSG density maps of our targets, where the relative star formation is confined to the dwarf's center.…”
Section: Spatial Distribution Of Stellar Populations As a Function Ofmentioning
confidence: 53%
See 1 more Smart Citation
“…4 we also report the age range covered by each evolutionary stage in our CMDs, although these are just estimates which do not take into account the spread of stars due to photometric errors. The youngest populations (a few Myr up to ∼100 Myr) in dwarf irregular galaxies are generally found in concentrated, actively star forming regions, which are located in the center as well as in offset knots (see, e.g., van Dyk et al 1998;Glatt et al 2010). This is clearly observed in the MS and/or BL/RSG density maps of our targets, where the relative star formation is confined to the dwarf's center.…”
Section: Spatial Distribution Of Stellar Populations As a Function Ofmentioning
confidence: 53%
“…This is clearly observed in the MS and/or BL/RSG density maps of our targets, where the relative star formation is confined to the dwarf's center. Active star forming regions tend to turn on and off in adjacent cells with time in a stochastic propagation fashion, with star forming complexes having lifetimes on the order of 10 2 Myr and sizes of up to some hundreds of pc in diameter (Seiden et al 1979;Dohm-Palmer et al 1997;Grebel & Brandner 1998;Dohm-Palmer et al 2002;Weisz et al 2008;Glatt et al 2010;Crnojević et al 2011a). Interestingly, the triangular shape of KK182 comes from an offset knot of star formation which is clearly recognized as a local enhancement in its MS and BL density maps, while it fades away in the RSG map.…”
Section: Spatial Distribution Of Stellar Populations As a Function Ofmentioning
confidence: 99%
“…They conclude that the last tidal interaction between the MCs has triggered the formation of both clusters and field stars. Moreover, Glatt et al (2010) find two periods of enhanced cluster formation at 125 Myr and 800 Myr in the LMC and at 160 Myr and 630 Myr in the SMC. The cluster ages were determined by fitting Padova and Geneva isochrones.…”
Section: Introductionmentioning
confidence: 80%
“…The ages of young star clusters given in Glatt et al (2010) is overplotted on the LSFE maps in Fig. 23.…”
Section: Comparison With the Hi Gas Distribution And Star Clustersmentioning
confidence: 99%
“…In contrast to , Noel et al (2009) did not find any quiescent epoch at the intermediate ages. Glatt et al (2010) studied the SFH of both the clouds based on star clusters with age <1 Gyr. They found that the cluster formation peaks at 160 Myr and 630 Myr for the SMC and 125 Myr and 800 Myr for the LMC.…”
Section: Introductionmentioning
confidence: 99%